Horse Racing: A Traditional Game to Improve Children’s Motor Gross Skill (Ethnopedagogy study on Dompu Tribe) - Ihlas Ihlas; Yufiarti Yufiarti; Edwita Edwita (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
Gross motor encompasses all abilities of coordination, flexibelity, and balance. Children are given opportunities to play more energetically activities such us horse racing tradional game. Yet, the study aims to investigate the stages of early childhood Gross motor skill transition using traditional horse racing activities in the Dompu community of Indonesia. This research employs a qualitative approach by ethnographic methods. The research subjects consisted of six young jockeys aged 4-8 years old and seven horse owners. The data were gathered through observation, interviews, and documentation, then analyzed using domain, taxonomic, compound and theme analysis techniques. The researchers found that the child jockeys go through three stages as their gross motor abilities improve and mature. The development of children's gross motor abilities begins with horse cleaning, river riding, and regular training in the horse racing arena. All of these stages are completed by youngsters with supervision of professionals or parents. Past research have shown that horseback riding may be used as a physical motor therapy intervention for children with special needs, such as autism and down syndrome.